Texts, songs, and sounds in post-1964 Brazil: the Opinião Theater Group on stage (Orfeu, 2020)
This text addresses the historical importance of the Opinião Theater Group (1965-1980) and its performances as political expressions of resistance to the Brazilian military dictatorship. Accordingly, I focus on how using musical discourse affects the audience not only through sound parameters, but also through its ability to suggest images and invent spaces and places by creating scenic-dramatic figurations. I highlight as the crucial characteristics of this musical theater the mix of cultural traditions and actors/singers’ artistic production/creation. Thus, it is relevant to discuss the counterpoint between musical and plastic languages in the composition of the polyphony that is inherent to theatrical performance.
Keywords: Opinião Theater Group; sounds; staging